A Mild and Regioselective Route to Functionalized Quinazolines. Issue 41 (19th August 2015) - Maiden, Tracy M. M.; Swanson, Stephen; Procopiou, Panayiotis A.; Harrity, Joseph P. A.
Abstract A Rh‐catalyzed ortho‐amidation cyclocondensation sequence gave a range of 4‐aminoquinazolines in high yield. The method features a remarkably mild C(sp2)H activation step and can be exploited to rapidly access compounds with established biological activity.